Protein kinase CK2 triggers cytosolic zinc signaling pathways by phosphorylation of zinc channel ZIP7 - Taylor, Kathryn M; Hiscox, Stephen; Nicholson, Robert I; Hogstrand, Christer; Kille, Peter (Science signaling, 2012)
The transition element zinc, which has recently been identified as an intracellular second messenger, has been implicated in various signaling pathways, including those leading to cell proliferation. Zinc channels of the ZIP (ZRT1- and IRT1-like protein) family [also known as solute carrier family 39A (SLC39A)] transiently increase the cytosolic free zinc (Zn(2+)) concentration in response to extracellular signals. We show that phosphorylation of evolutionarily conserved residues in endoplasmic reticulum zinc channel ZIP7 is associated with the gated release of Zn(2+) from intracellular stores, leading to activation of tyrosine kinases and the phosphorylation of AKT and extracellular signal-regulated kinases 1 and 2. Through pharmacological manipulation, proximity ligation assay, and mutagenesis, we identified protein kinase CK2 as the kinase responsible for ZIP7 activation. Together, the present results show that transition element channels in eukaryotes can be activated posttranslationally by phosphorylation, as part of a cell signaling cascade. Our study links the regulated release of zinc from intracellular stores to phosphorylation of kinases involved in proliferative responses and cell migration, suggesting a functional role for ZIP7 and zinc signals in these events. The connection with proliferation and migration, as well as the activation of ZIP7 by CK2, a kinase that is antiapoptotic and promotes cell division, suggests that ZIP7 may provide a target for anticancer drug development.